Koncepční návrh elektrického výcvikového letounu - Seman, Matúš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Predkladaná diplomová práca je venovaná koncepčnej fáze návrhu výcvikového letúna s elek-trickým pohonom certifikovaného v rámci predpisu CS-LSA. Návrhový proces geometrických a aerodynamických parametrov sa primárne opiera o štatistický rozbor stávajúcich letúnov v danej kategórii. Následný výpočet letových vlastností a letových výkonov je založený na znalosti aerodynamickej poláry, ktorej určenie je predmetom tejto práce. Poslednou časťou práce je konštrukčný návrh prednej časti trupu a pevnostný návrh motorových lóží.

This thesis is focused on conceptual design of electric powered training aircraft, using certification guidelines CS-LSA. Designing process of geometrical and aerodynamic characteristics is primary based on statistics of certificated aircrafts in this particular category. The following calculation of performance stabilities and flight performances is based on knowledge of aerodynamic polar. The calculation of the polar is also part of this thesis. The last part of the thesis consists of construction design of the front part of fuselage and engine static structural analysis of engine mounts.
Conceptual design of training aircraft with electric propulsion
Keywords: koncepčný návrh; CS-LSA; polára; letové výkony; motorové lóže; conceptual design; CS-LSA; polar; flight performances; engine mounts